Pendidikan Multikulturalisme Di Era Modern (Dialektika Kritis Pendidikan Islam Monokotomik) - Jasmani, Jasmani (Jurnal Studi Agama dan Masyarakat, 2015)
Â Monokotomic education is the educational system construction of the plenary which is capable of integration educational value of domain-oriented humanitarian and religious by a nature.The education system also implies an attitude of valuing differences in values, norms, culture and tradition (Multiculturalism) as well as of the religious aspect of pluralism as a consequence of the Muslims. Therefore, there needs to be a paradigm in education it is necessary to elaborate on the elements of cultural pluriformity become construction between the wisdom or community â read the culture. It is intended as an attempt to construct a more civilized society structure, harmonious, and prosperous with cache while respecting cultural differences. Konstruks education is believed to be supporting the formation of communities of multiculturalism and pluralism in this modern era; where the whole community with all the elemental sued for bears fate and interdependence together for the creation of a lasting peace. Therefore, education (Islamic) multiculturalism with the paradigm of monokotomic need to be constructed which will later put forward positional egalitarian culture system at all, so its able to eliminate the superiority-inferiority between one culture and other cultures.